Thermal analysis of borogypsum and its effects on the physical properties of Portland cement - Elbeyli, IY; Derun, EM; Gülen, J; Piskin, S (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Borogypsum, which consists mainly of gypsum crystals, B2O3 and some impurities, is formed during the production of boric acid from colemanite, which is an important borate ore. In this study, the effect of borogypsunt and calcined borogypsum on the physical properties of ordinary Portland cement (OPC) has been investigated. The calcination temperature and transformations in the structures of borogypsunt and natural gypsum were determined by differential thermal analysis (DTA), thennogravimetric analysis (TGA) and X-ray diffraction (XRD) techniques. Thermal experiments were carried out between ambient temperature and 500 degreesC in an air atmosphere at a heating rate of 10 degreesC min(-1). After calculation of enthalpy and determination of conversion temperatures, borogypsum (5% and 7%), hemihydrate borogypsum (5%) and natural gypsum (5%) were added separately to Portland cement clinker and cements were ground in the laboratory. The final products were tested for chemical analysis, compressive strength, setting time, Le Chatelier expansion and fineness properties according to the European Standard (EN 196). The results show that increasing the borogypsurn level in Portland cement from 5% to 7% caused an increase in setting time and a decrease in soundness expansion and compressive strength. The cement prepared with borogypsum (5%) was found to have similar strength properties to those obtained with natural gypsum, whereas a mixture containing 5% of hermhydrate borogypsum was found to develop 25% higher compressive strength than the OPC control mixtures at 28 days. For this reason, utilization of calcined borogypsum in cement applications is expected to give better results than untreated borogypsum. It is concluded that hemihydrate borogypsum could be used as a retarder for Portland cement as an industrial side. This would play an important role in reducing environmental pollution. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: Portland cement; thermal analysis; X-ray diffraction; physical properties; mechanical properties; borogypsum; BEHAVIOR; PHOSPHOGYPSUM; GYPSUM; BORON; Construction & Building Technology; Materials Science